2003
DOI: 10.1080/09593330309385559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of packing material on the biofiltration of benzene, toluene and xylene vapours

Abstract: Biofiltration was used to eliminate volatile organic compounds from air streams in bench-scale reactors inoculated with an adapted consortium. Organic and inert supports were tested on 100 days of operation. The supports were: peat, vermiculite, a mixture of vermiculite and activated carbon, tree bark and, porous glass Rashig rings. A mixture of benzene, toluene and xylene vapors with a load of 200 gC m(-3) h(-1) was fed to the biofilters with an empty bed residence time of 60 s. Removal efficiencies higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…If elimination capacities remain constant, the increase in carbon dioxide concentration can be only attributed to the microorganisms, which are also able to oxidize the organic matter previously adsorbed on the surface of the material. In this sense, Ortiz et al (2003) affirmed that sorption can favor the contact between microorganisms and the pollutants.…”
Section: Sorption and Biodegradation Processes Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…If elimination capacities remain constant, the increase in carbon dioxide concentration can be only attributed to the microorganisms, which are also able to oxidize the organic matter previously adsorbed on the surface of the material. In this sense, Ortiz et al (2003) affirmed that sorption can favor the contact between microorganisms and the pollutants.…”
Section: Sorption and Biodegradation Processes Interactionmentioning
confidence: 99%
“…Abumaizar et al (1998) showed that biofilters containing granular activated carbon exhibited significantly higher removal efficiencies and more stable operation during sudden load increases than biofilters containing only compost. Ortiz et al (2003) studied the effect of the presence of activated carbon in a vermiculite-based biofilter observing positive effects in the removal efficiencies. Dorado et al (2009) demonstrated that a sludge-based carbon with a high capacity to smooth inlet load changes was a good support to immobilize and grow the biomass obtaining relative good removal efficiencies (up to 90%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following 32 days of operation, the system was loaded by the air flow rate with a constant toluene inlet concentration of 100 mg.m -3 (Fig. 3) (Morales et al, 1998), compost (Delhomenie et al, 2003, vermiculite (Ortiz et al, 2003), perlite (Arriaga and Revah, 2005), activated carbon (Li et al, 2002 . Therefore, an EBRT of 35s was the optimal value for this system, with respect to sufficient air cleaning at a good elimination capacity of 7.5 g C .m…”
Section: Resultsmentioning
confidence: 99%
“…Although the cost of inert filter beads, in most cases, is higher compared to that of organic counterparts, the former have a range of advantages: chemical and physical inactivity, long lifetime, high performance, more regular shape, uniform air distribution, and reduced number of channeling issues. In addition, inert carriers are also much easier to clean and replace [1,9,14]. Porous ceramic beads have also been shown to be an appropriate packing material for biofilters due to their high gas and liquid film mass transfer coefficients [12].…”
Section: Introductionmentioning
confidence: 99%